Hak Untuk Melakukan Perdamaian di Perairan Laut Indonesia Dilihat Dari Hukum Internasional - Mardiyati, Siti (Sekolah Tinggi Ilmu Hukum sumpah Pemuda, 2024)
Each State has the right to navigate in its own territorial waters, in the open sea, and in the territorial water of another State. Requirements for the implementation of the right of peaceful navigation in Indonesian waters based on the domestic laws of Indonesia. However, the sovereignty of the coastal State remains bound by the provisions of the Convention itself and other international law.